2012
DOI: 10.1111/j.1365-313x.2012.05008.x
|View full text |Cite
|
Sign up to set email alerts
|

Unpredictability of nectar nicotine promotes outcrossing by hummingbirds in Nicotiana attenuata

Abstract: SUMMARYMany plants use sophisticated strategies to maximize their reproductive success via outcrossing. Nicotiana attenuata flowers produce nectar with nicotine at concentrations that are repellent to hummingbirds, increasing the number of flowers visited per plant. In choice tests using native hummingbirds, we show that these important pollinators learn to tolerate high-nicotine nectar but prefer low-nicotine nectar, and show no signs of nicotine addiction. Nectar nicotine concentrations, unlike those of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 64 publications
(81 reference statements)
3
109
0
Order By: Relevance
“…Clear supernatant was collected and analyzed using a HPLC/ESI-Q3-MS (Varian 1200) with 35V capillary voltage as described previously (46). Analysis of Cotinine, CNO and NNO.…”
Section: Methodsmentioning
confidence: 99%
“…Clear supernatant was collected and analyzed using a HPLC/ESI-Q3-MS (Varian 1200) with 35V capillary voltage as described previously (46). Analysis of Cotinine, CNO and NNO.…”
Section: Methodsmentioning
confidence: 99%
“…However, in flowers their levels are relatively low, and in the case of nicotine, their concentrations change between day and night (68), and in nectar, nicotine occurs at highly variable and unpredictable concentrations that function to increase the outcrossing behavior of hummingbird pollinators (69). Given that high nicotine levels in flowers repel pollinators in N. attenuata (70), we speculate that high levels of HGL-DTGs or phenolamides in flowers might have similar effects.…”
Section: Discussionmentioning
confidence: 94%
“…As previously reported, constitutively produced defense metabolites such as nicotine, rutin, and chlorogenic acid exhibit comparatively low degrees of natural variation. Not only is nicotine a direct defense compound effective against attack by leaf herbivores but its occurrence in the nectar also affects pollinator visits and outcrossing rates (37,39); as such, stronger selection pressures are expected to erode large quantitative variations in nicotine levels. However, recent work has shown that yet to be identified molecular mechanisms generate high variations in nectar nicotine concentrations that surpass variations found in vegetative tissues (37).…”
Section: Resultsmentioning
confidence: 99%
“…Not only is nicotine a direct defense compound effective against attack by leaf herbivores but its occurrence in the nectar also affects pollinator visits and outcrossing rates (37,39); as such, stronger selection pressures are expected to erode large quantitative variations in nicotine levels. However, recent work has shown that yet to be identified molecular mechanisms generate high variations in nectar nicotine concentrations that surpass variations found in vegetative tissues (37). This previous result suggests that independent mechanisms may control the variability of nicotine concentrations in these two compartments of a plant.…”
Section: Resultsmentioning
confidence: 99%